Microvascular oxygen extraction during competitive alpine skiing with regard to loaded and unloaded phases - Stöcker, F.; Goll, M.; Fus, V.; Spitzenpfeil, P. (Science and Skiing VII, 2018)
Our data underline that aerobic contribution to energy metabolism in competitive alpine skiing is remarkable, despite the undoubtedly high ground reaction forces and the concomitant demand on the anaerobic system. This pilot study aimed to be a first approach to the question of how oxygen uptake kinetics can influence competitive skiing performance and what the influences of local muscle perfusion are. Therefore, we suggest considering unloaded phases as representative grid points for perfusion parameters rather than loaded phases because the latter are affected by mechanical compression of the muscle. For subsequent studies, oxygen uptake measurements should be conducted in race-like conditions.